2015
DOI: 10.26522/brocked.v24i2.395
|View full text |Cite
|
Sign up to set email alerts
|

Well-being and human-animal interactions in schools: The case of "Dog Daycare Co-Op"

Abstract: This study draws on Martha Nussbaum's (2000)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…If a student is able to be calm, gentle, and caring toward the therapy dog, the student learns how to model these behaviors at other times as well: "Once (children) developed emotional connections with the animals and learned to care for them, experiencing the same empathy when interacting with people became significantly less challenging" (p. 208). Research by Pinto and Foulkes (2015) supports this theory and furthers it by finding the feeling of compassion students had for the dog carried through to a feeling of compassion for peers. Similarly, a qualitative study by Daly and Suggs (2010) investigated the use of animals in the classroom and further purports that the presence of the animal in the classroom strengthened students' sense of empathy; one teacher recalled "when the class heard that Rocky had died over the summer, one girl brought me in a sympathy card and a stuffed (animal)" (p. 105).…”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations
“…If a student is able to be calm, gentle, and caring toward the therapy dog, the student learns how to model these behaviors at other times as well: "Once (children) developed emotional connections with the animals and learned to care for them, experiencing the same empathy when interacting with people became significantly less challenging" (p. 208). Research by Pinto and Foulkes (2015) supports this theory and furthers it by finding the feeling of compassion students had for the dog carried through to a feeling of compassion for peers. Similarly, a qualitative study by Daly and Suggs (2010) investigated the use of animals in the classroom and further purports that the presence of the animal in the classroom strengthened students' sense of empathy; one teacher recalled "when the class heard that Rocky had died over the summer, one girl brought me in a sympathy card and a stuffed (animal)" (p. 105).…”
Section: Introductionmentioning
confidence: 87%
“…Interestingly, most of the literature regarding pet therapy in schools is written through the lens of the counselor (Coyne-Foresi, 2015;Firmin et al, 2016;Jenkins et al, 2014;Weston, 2010) or educator (Beetz, 2013;Daly & Suggs, 2010;Friesen, 2010;Kirnan et al, 2016;Pinto & Foulkes, 2015). None of the search results for this review yielded research on pet therapy through the lens of the school nurse.…”
Section: Role Of the School Nursementioning
confidence: 99%
See 1 more Smart Citation
“…One benefit that has been highlighted consistently across studies is the health benefit of HAIs, as there are diverse studies that have shown that interacting (physically, cognitively, or affectively) with pets typically reduces depression symptoms, the stress triggered by negative events, and loneliness [28]. Moreover, HAIs, such as taking a walk with the pet, act like an "ice-breaker" as this catalyzes communication and enhances opportunities for social exchange, which in turn enhance social interaction or social skills and promote the feeling of social integration [4,10,[32][33][34]. Research has also shown that the simple act of looking at the pet decreases anxiety and exerts a calming or dearousing influence [33].…”
Section: The Importance Of Petsmentioning
confidence: 99%
“…The purpose of AAAs in schools is to encourage children to increase their social interactions, participate in education, and modify their behavior. An equally important aim of AAAs is also its effect as a preventive factor against risky behavior, and, at the same time, a mediator facilitating introverted students to interact with classmates and get more involved in the course of education [27]. The presence of a specially trained dog may have a beneficial effect on the climate of the whole class [28].…”
Section: Introductionmentioning
confidence: 99%